Conceptual Issues of National Security Policy-Making Under Uncertainty - Reznikova, Olga; Smolianiuk, Volodymyr (Politologija, 2023)
The article examines the nature of the uncertainty impact on the formation and implementation of national security policy. The multiplication of uncertainties and complication of the system of social relations prompt a transformation of conceptual approaches to the identification of the national security basic features and the organization of key processes in this area. It has been proven that the development of the concepts of uncertainty and resilience prompts a reconceptualization of the national security. This process is currently taking place. The implementation of new approaches to ensuring national security contributed to the initiation of a paradigm shift in national security policy. Management of uncertainty allows for reducing its influence on national security policy-making. The development of science and increasing the level of public trust in scientific information, which is taken as a basis for shaping political decisions, are of great importance for this.